2007
DOI: 10.1200/jco.2006.06.6506
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Rates After Year 2000 Significantly Decrease in Children With Perinatal HIV Infection: A Study by the Italian Register for HIV Infection in Children

Abstract: Dramatically reduced cancer rates were observed only in the late HAART period in parallel to the increasing proportion of children receiving HAART therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 15 publications
4
32
1
3
Order By: Relevance
“…22 Our incidence rates are lower than estimates from previous studies done in HIV-positive children in Europe and the US, see Table 5 . 3, 4, 9 It is difficult to directly compare studies because of different study designs, settings and populations. The US AIDS cancer match study 2, 4 only included children diagnosed with AIDS, while the Italian HIV Registry 9, 23 and our study also included children with HIV that had not yet progressed to AIDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Our incidence rates are lower than estimates from previous studies done in HIV-positive children in Europe and the US, see Table 5 . 3, 4, 9 It is difficult to directly compare studies because of different study designs, settings and populations. The US AIDS cancer match study 2, 4 only included children diagnosed with AIDS, while the Italian HIV Registry 9, 23 and our study also included children with HIV that had not yet progressed to AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…5-8 Studies from Europe and the United States of America (USA) have shown that the incidence of cancer has declined as combination antiretroviral therapy (ART) has become more widely available. 3, 4, 9 Cohort studies of HIV-positive children are rare in the African region, and no study has so far assessed the impact of ART on the risk of developing cancer. 10 Moreover, data collection is often restricted to AIDS-defining cancers, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…4 In the advent of antiretroviral therapy, the incidence of AIDS-defining cancers in children has decreased dramatically 5 , but that of non-AIDS-defining cancers has continued to rise. Epidemiological data suggest that antiretroviral therapy may reduce the incidence of AIDS-defining cancers in children because of improved immunosurveillance induced by antiretroviral therapy.…”
Section: To the Editorsmentioning
confidence: 99%
“…10 -13 However, the increase in life expectancy has led to a change in the risk of developing HIV-associated malignancies. 14 The aim of our study was to evaluate changes in the patterns of cancer rates in HIV-infected children on HAART for over a decade of follow-up during 3 different periods (early-period HAART: 1997HAART: -1999 …”
mentioning
confidence: 99%